2007
DOI: 10.1038/bdj.2007.224
|View full text |Cite
|
Sign up to set email alerts
|

Lasers and soft tissue: periodontal therapy

Abstract: • Laser use in periodontology includes the removal of intra-pocket diseased epithelium, bacterial and calculus accumulation and in the surgical correction of infra-and intra-bony pocketing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
(36 reference statements)
0
33
0
2
Order By: Relevance
“…It is a solid state soft tissue laser with GaAlAs as the medium coming under the laser classification of IV. 4 A 400 mm surgical disposable tip was initiated prior to using it for excision of the overgrowth. All universal precautions of laser safety were followed prior and during the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…It is a solid state soft tissue laser with GaAlAs as the medium coming under the laser classification of IV. 4 A 400 mm surgical disposable tip was initiated prior to using it for excision of the overgrowth. All universal precautions of laser safety were followed prior and during the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Retreatments should follow at weekly intervals during the maximum four week period. [13] x.iii Diode Laser in Implantology Dental diode laser can be used for second stage implant recovery and the treatment of peri-implantitis. In second stage implant recovery care must be exercised to avoid contact with the implant body.…”
Section: XII Periodontal Therapy With Diode Lasermentioning
confidence: 99%
“…Some studies have shown a good clinical outcome and microbial advantages. These include prevention against subgingival biofilm formation, a decrease in the number of bacteria, and the removal of plaque, calculus, and endotoxins [2,3]. According to the results, the clinical improvement following SRP is promising, but the bacteria remaining in the pocket can colonize and can be detected in a short time [2].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of a low-dose laser has been considered, as it aims to eliminate the bacteria from periodontal patient, it is easy to use a dentist in caring for and maintaining oral health [3,5]. Some researchers are trying to find alternative care options to reduce the use of antibiotics and other chemicals in the treatment of periodontitis, one of which is low-dose laser therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation